Disponibilidade hídrica e sazonalidade sobre a fitomassa, anatomia foliar e produção de óleo essencial de cidró - Thiesen, Leonardo Antonio (2019)
Seasonality and water availability are environmental factors that directly influence the growth, development and production of secondary metabolites in aromatic plants. The objective of the study was to evaluate phytomass production, photosynthetic pigments, stomatal and trichome density, yield, content and characterization of the essential oil composition of Aloysia triphylla plants in response to different water availability and seasonality. The research was developed in the period of 2015 and 2017, in protected environment in the experimental area of the Federal University of Santa Maria, Campus Frederico Westphalen. The experimental design was a randomized complete block design in a 4x4 factorial scheme, consisting of four levels of water availability: 25%, 50%, 75% and 100% of field capacity during the autumn, winter, spring and summer seasons. The water availability control was carried out by means of the daily weighing of the pots, and the irrigations with different water availability were started in the middle of each season. They were evaluated at the end of each season: plant height, phytomass (fresh and dry mass of branches, fresh and dry leaf mass and leaf area), photosynthetic pigments (Chlorophyll a, chlorophyll b and carotenoids), stomatal density and glandular trichomes, yield, content and characterization of the chemical composition of the essential oil. It was observed that phytomass was significantly higher during spring cultivation and with higher water availability, while autumn and winter seasons, as well as lower water availability, negatively affected plant growth. The highest content of photosynthetic pigments and stomatal density were also higher in the spring season. The highest densities of glandular trichomes were found in the abaxial portion of the leaves during winter and summer. In addition, higher yields of essential oil were observed in the spring season with higher water availability, followed by summer, while higher content was observed during the winter with low water availability. The chemical characterization of the essential oil made it possible to identify more components in the summer. However, higher concentrations of the major components were obtained with low water availability in the winter. It is concluded that in spring there is a higher content of photosynthetic pigments and higher stomatal density, indicating better responses by plants. In addition, the spring season with higher water availability is indicated for higher phytomass production and yield of essential oil. The density of glandular trichomes increases in the winter and summer seasons. The increase in the content and concentration of the major components α-citral and β-citral occur in winter under low water availability. In the summer crop, a greater quantity of chemical components occurs, and less water availability reduces the concentration of α-citral and β-citral components, significantly increasing the concentration of caryophyllene oxide.